Irregular Transition Layer Beneath the Earth's Inner Core Boundary From Observations of Antipodal PKIKP and PKIIKP Waves. (3rd October 2018) - Attanayake, Januka; Thomas, Christine; Cormier, Vernon F.; Miller, Meghan S.; Koper, Keith D.
Abstract: Standard Earth models assume a simple uniform inner core boundary (ICB) separating the liquid iron outer core from the solid iron inner core. Metallurgical and geodynamic experiments, however, predict lateral variations along this boundary originating from thermochemical and geodynamic instabilities during solidification. We search for evidence of this lateral heterogeneity by exploiting the sensitivity of antipodal PKIIKP waveforms to the shear wave velocity structure of the uppermost inner core beneath their reflection points on the underside of the ICB. Measuring PKIIKP/PKIKP energy ratios from 33 rare antipodal seismograms in the 178 o to 180 o distance range, we find this ratio varying between 0.1 and 1.1. Synthetic seismograms demonstrate that a laterally homogeneous liquid‐solid ICB cannot account for this variability. Observations instead support a spatially variable ICB transition consisting of either (1) gradients in seismic velocities and density in which they smoothly increase from those at the outer core to those in the bulk of the inner core over a maximum depth of 10 km or (2) a layered transition with localized double discontinuities in velocities and densities separated by 4–10 km. A layered transition can generate a coda following PKIKP if shear velocity is small (<2 km/s) in the transition. Our results imply that the ICB is not uniform and might appear patchy with lateral rigidity variations. Nonuniform small‐scale structural features that we infer to be present at the ICB are consistent with nonlinear solidification mechanisms driven by small‐scale outer core convection in the lowermost outer core. Plain Language Summary: The Earth's core is divided into an outer liquid iron core and an inner solid iron core, where the latter freezes from the former. This growth process is not well understood because creating extreme physical and chemical conditions present in the deep interior in laboratories is difficult. Much of the knowledge about the inner core thus is indirectly obtained by modeling seismic waves traveling through it. Here we use a rare data set, where the seismic waves are recorded at stations nearly diametrically opposite to earthquakes, to constrain seismic structure near the inner core boundary. We find that amplitudes of waves that are reflected once from the underside of this boundary (PKIIKP) show rapid lateral variations relative to the waves that directly go through the inner core (PKIKP). We show that such variability can arise if the shear velocity structure—proxy to rigidity—in the vicinity of the inner core boundary is also varying. Our results, therefore, suggest that outer‐to‐inner core transition is not sharp but is characterized by a thin layer of varying rigidity and thickness. This indicates that the growth of the inner core is nonuniform and coupled to small‐scale convection present at the bottom of the outer core. Key Points: PKIIKP/PKIKP energy ratios are measured from a rare global data set of 33 antipodal seismograms PKIIKP/PKIKP energy ratios vary at short length scales ( 200 km) along the inner core boundary, implying variations in shear velocity The presence of a nonuniform transition layer could explain lateral variations of shear velocity